Physical therapy for survivors of torture: A scoping review - Dee, Justine McCuen; Gell, Nancy; van Eeghen, Constance; Littenberg, Benjamin (Torture Journal, 2024)
Background: Torture can result in impaired function, reduced quality of life, and chronic pain. Physical therapy (PT) is recommended for wholistic care of survivors of torture (SOT), however there are limited evidenced-based guidelines. We conducted a scoping review to identify and describe the approach and gaps in knowledge around the PT treatment of SOT. Methods: We adhered to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews. Nine databases were searched from inception to 2023. Eligible sources were those involving PT treatment for SOT. Extracted data included the source of evidence, PT description, mode of delivery, and research study outcomes. Interventions were categorized into themes based on recommendations from the Physiotherapy and Refugees Education Project: trauma-informed care, body-awareness & empowerment, and pain management. Source-reported treatment approach and expected effect of the interventions informed the thematic categorization. Results: The final analysis included thirteen sources with a combined total of 18 different interventions. Thematically, two sources described interventions targeting body-awareness & empowerment, while five sources targeted body-awareness & empowerment and pain management. Six sources included all three themes. Two of these six sources were research studies examining PT outcomes. Findings were significant favoring the PT, but results must be taken cautiously due to methodological limitations. Studies assessing treatment related to only one theme resulted in no between group differences. Conclusions: We describe the scope of the literature regarding PT for SOT. A trauma-informed PT approach, coordinated with pain management, and body-awareness & empowerment interventions may address the complex needs of survivors. However, rigorous studies of this approach are lacking. As the number of displaced persons continues to rise globally, we must be prepared to care for these vulnerable people. Physical therapists are encouraged to utilize a wholistic approach, and to examine outcomes of this approach for survivors of torture.